Low distortion micropower filterless digital class D amplifier - Rajagopalan Ananthkrishnan (2008)
This report investigates the concept, design and implementation of a filterless Class D amplifier, for digital hearing instrument applications. The traditional Class D amplifier requires a low pass filter to eliminate the switching currents and the high frequency components. The filter accounts for a major part in the cost of the Class D amplifier, and thus by eliminating the filter the cost can be minimized and the product can be made competitive.